1989
DOI: 10.1164/ajrccm/140.5.1436
|View full text |Cite
|
Sign up to set email alerts
|

Chylothorax: A Complication of the Nephrotic Syndrome

Abstract: A 50-yr-old man with the nephrotic syndrome developed a chylothorax that was shown to be due to transdiaphragmatic movement of chylous ascites. Because a significant number of patients with nephrotic syndrome have been reported to have chylous ascites, the possibility that chylothorax is due to movement of chylous ascites into the pleural space should be considered prior to surgical intervention directed toward repair of the thoracic duct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 4 publications
1
19
0
Order By: Relevance
“…In the case reported here, the appearance of radionucleotide tracer in the pleural space after intraperitoneal injection confirmed that the cause of chylothorax was the flow of fluid across the diaphragm rather than diaphragmatic lymphatics. To our knowledge, this is the third reported case of chylothorax from chylous ascites in a nephrotic patient [2,3]. Interestingly, chylothorax in these three cases was identified exclusively in adults and presented only in the right hemithorax.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…In the case reported here, the appearance of radionucleotide tracer in the pleural space after intraperitoneal injection confirmed that the cause of chylothorax was the flow of fluid across the diaphragm rather than diaphragmatic lymphatics. To our knowledge, this is the third reported case of chylothorax from chylous ascites in a nephrotic patient [2,3]. Interestingly, chylothorax in these three cases was identified exclusively in adults and presented only in the right hemithorax.…”
mentioning
confidence: 62%
“…The nephrotic syndrome is known to be associated with chylous ascites [2,3]. In one early series involving nephrotic patients with hydroperitoneum, chylous ascites was documented in 52% of cases [4].…”
mentioning
confidence: 99%
“…Whether these measures play the same role in the treatment of secondary chylothorax as they do in primary chylothorax is not known. They do not reduce the flow of chyle, but drainage can improve ventilation, and sclerosis of the diaphragmatic pleura may increase the barrier to leakage of ascitic fluid, thereby preventing reaccumulation of pleural fluid [14].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the ascitic characteristics were not examined. To our knowledge, the complication of chyloperitoneum and/or chylothorax is rarely noticed in adult nephrotic patients [2][3][4][5][6], and clinical and laboratory features of chylous ascites remain to be determined. We herein reported an elderly patient with nephrotic syndrome due to membranous nephropathy, who presented chylous ascites.…”
mentioning
confidence: 99%
“…To our knowledge, except for the initial description [1], the complication of chyle has been reported in only 4 cases with adult nephrotic syndrome [2][3][4][5]. The characteristics of ascitic chyle are always associated with elevated triglyceride levels from 90 to 529 mg/dl and low cholesterol levels from 10 to 62 mg/dl [2][3][4][5][6].…”
mentioning
confidence: 99%